2016
DOI: 10.1016/j.paid.2016.04.022
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive emotion regulation and psychopathology across cultures: A comparison between six European countries

Abstract: Witthöft, M., and Kraaij, V. (2016of the relationships between specific strategies and symptoms of psychopathology was consistent across countries. Although there were cross-cultural differences in the use of cognitive strategies, the consistent relationship between strategies and psychopathology across countries supports the idea of a trans-cultural approach to treating psychopathology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
61
0
10

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(80 citation statements)
references
References 36 publications
9
61
0
10
Order By: Relevance
“…), and the method of consumption (ingestion, inhalation, smoking, intravenous and nonvenous injections). The other three questionnaires included the Beck depression inventory (Cronbach's alpha coefficient: 0.9) (11), the World Health Organization Quality of Life Questionnaire (WHOQOL-26) in four domains of physical health, psychological health, social relationship, and environment (Cronbach's alpha coefficient: > 0.7) (12), and Spielberger Anxiety Inventory (Cronbach's alpha coefficient: 0.86 -0.95) (13). According to the Beck Depression Inventory, people with a score of less than 16 have no depression, 17 -25 have mild depression, 26 -34 have moderate depression, and more than 34 have severe depression.…”
Section: Methodsmentioning
confidence: 99%
“…), and the method of consumption (ingestion, inhalation, smoking, intravenous and nonvenous injections). The other three questionnaires included the Beck depression inventory (Cronbach's alpha coefficient: 0.9) (11), the World Health Organization Quality of Life Questionnaire (WHOQOL-26) in four domains of physical health, psychological health, social relationship, and environment (Cronbach's alpha coefficient: > 0.7) (12), and Spielberger Anxiety Inventory (Cronbach's alpha coefficient: 0.86 -0.95) (13). According to the Beck Depression Inventory, people with a score of less than 16 have no depression, 17 -25 have mild depression, 26 -34 have moderate depression, and more than 34 have severe depression.…”
Section: Methodsmentioning
confidence: 99%
“…Sample items include “I think that I have to accept the situation” and “I am preoccupied with what I think and feel about what I have experienced.” The CERQ has demonstrated adequate reliability and validity (Garnefski & Kraaij, ). For the purposes of the current studies, we additionally summed the positive subscales (acceptance, positive refocusing, refocus/planning, positive reappraisal, and putting into perspective) and negative subscales (self‐blame, rumination, catastrophizing, and other blame) to produce two composite scores representing theoretically more and less adaptive cognitive coping responses, following Potthoff et al ().…”
Section: Study 1: Methodsmentioning
confidence: 99%
“…Regarding irrational beliefs cross-culturally, studies have focused on investigating cross-cultural differences in the use of cognitive strategies and on testing whether the relationship between specific strategies and psychopathology varies across countries. A recent study [39] found that there were differences in strategies that have been associated with symptoms of psychopathology; overall, Northern European countries (Germany and the Netherlands) had less use of rumination, catastrophizing, and other-blame compared to Southern and Eastern European countries (Spain, Italy, Portugal, and Hungary) but not among southern countries.…”
Section: Cross-cultural Differences On Studies Variablesmentioning
confidence: 99%